Preponderância da dinâmica hidrológica sobre a sincronia e padrões de diversidade beta de comunidades zooplanctônicas - Lopes, Vanessa Guimarães (2015)
Several studies have shown that spatial synchrony is a ubiquitous pattern, occurring in different regions, types of ecosystems and in different groups of organisms. Spatial synchrony has important implications for the persistence of populations. Another implication is the possibility of using local "sentinels" sites, assuming regionalized or synchronous dynamics over the whole area of interest. In this context, our work uses a long-term (8 years) data set to quantify the level of synchrony between local zooplankton populations in a tropical reservoir. We expect high synchrony due to high connectivity as well as due to the Moran effect. Population synchrony was negatively correlated with geographic distance. However, population synchrony declined more consistently with environmental distance and environmental synchrony than with geographic distance. Besides, our results suggested that main variables driving synchrony were those correlated with hydrological conditions. Geographic distance was more important for protozoans, while the population synchrony of the other zooplankton groups was strongly driven by environmental synchrony. Furthermore, we found a decrease of environmental synchrony with the increase of geographical distance between points. Our results suggest that the strength of the Moran’s effect may be underestimated when simple environmental distances are used. We suggest that further studies should allow for environmental synchrony instead of allowing only for environmental similarity. Finally, despite significant, population synchrony was not so high to justify a reduction in the number of sampling sites.